2012
DOI: 10.1128/aac.05418-11
|View full text |Cite
|
Sign up to set email alerts
|

In VivoImpact of Met221 Substitution in GOB Metallo-β-Lactamase

Abstract: Metallo-␤-lactamases (M␤Ls) represent one of the main mechanisms of bacterial resistance against ␤-lactam antibiotics. The elucidation of their mechanism has been limited mostly by the structural diversity among their active sites. All M␤Ls structurally characterized so far present a Cys or a Ser residue at position 221, which is critical for catalysis. GOB lactamases stand as an exception within this picture, possessing a Met residue in this location. We studied different mutants in this position, and we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 37 publications
3
23
0
Order By: Relevance
“…In addition, previous analyses of mutant GOB-18 Asp120Ser and metal-substituted GOB-18 derivatives showed that the Zn2 site is essential for catalysis and for the stabilization of an anionic intermediate in the hydrolysis of nitrocefin (29,57). On the other hand, even though replacement of Gln116 by an isosteric His residue was somewhat detrimental for the resistance profile conferred by GOB-18 (29,31), it had little effect on metal content or on the in vitro activity of dinuclear GOB-1 (30) and remetallated mono-Zn(II) GOB-18 (29). Indeed, mutations Gln116Asn and Gln116Ala, which are predicted to impact the structure of the Zn2 site through perturbations on the second coordination sphere (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, previous analyses of mutant GOB-18 Asp120Ser and metal-substituted GOB-18 derivatives showed that the Zn2 site is essential for catalysis and for the stabilization of an anionic intermediate in the hydrolysis of nitrocefin (29,57). On the other hand, even though replacement of Gln116 by an isosteric His residue was somewhat detrimental for the resistance profile conferred by GOB-18 (29,31), it had little effect on metal content or on the in vitro activity of dinuclear GOB-1 (30) and remetallated mono-Zn(II) GOB-18 (29). Indeed, mutations Gln116Asn and Gln116Ala, which are predicted to impact the structure of the Zn2 site through perturbations on the second coordination sphere (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GOB-18 was produced in the periplasmic space of E. coli C41(DE3) cells harboring the plasmid pKP-GOB-18 (29,31,32). This vector allows the production of recombinant GOB-18 as a C-terminal fusion to the leader peptide pelB (29,31).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All PCRs were carried out using Platinum Pfx DNA polymerase (Invitrogen) with the following thermal cycle: 3 min at 95°C, 30 cycles of 15 s at 95°C, 30 s at 55°C, and 1 min at 68°C, and 10 min at 68°C. The NDM-1 C26A mutant gene was generated from pMBLe-bla NDM-1 by site-directed mutagenesis, as described previously (12), using the primers NDM-1-C26A Fw (5=-CATTGATGCTGAGCGGGGCGATGCCCGGTGAAATC-3=) and NDM-1-C26A Rv (5=-GATTTCACCGGGCATCGCCCCGCTCAGCA TCAATG-3=). V-NDM-1 and N-VIM-2 were constructed by overlapextension PCR using the overlapping primers VIM2-B (5=-ATTC GGTGCGAGCTGGCGGAAAACCAGATCCCCGACCGGAATTTC GC-3=), NDM1-C (5=-GATCTGGTTTTCCGCCCAGCTCGCAC CG-3=), NDM1-D (5=-ACCATCGGCAATCTGGTAAAGCCGGACCT CGCCAAACCGTTGGTCGCC-3=), and VIM2-E (5=-GAGGTCCGGC TTTACCAGATTGCCG-3=), with external primers VIM2NdeI Fw , NDM1NdeI Fw , VIM2StHindIII Rv , and NDM1StHindIII Rv .…”
Section: Bacterial Isolates (I) Isogenicmentioning
confidence: 99%